Η διερεύνηση της αποτελεσματικότητας της χρήσης του μελιού στην αντιμετώπιση της ξηροστομίας και της στοματοβλεννόγοντπδας σε πάσχοντες με κακοήθεια κεφαλης και τράχηλου που υποβάλλονται σε ακτινοθεραπεία - Χαραλάμπους, Μέλανη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Background: The head and neck malignancy is one of the most serious forms of malignancy with multidimensional effects on all aspects of the quality of life of patients, with a focus on the physical effects such as dry mouth and oral mucositis. Combination therapy between conventional and alternative medicine like honey shows encouraging results since so far there is no effective treatment for these side effects. However, the efficacy of adjunctive therapy through the existing literature is inconsistent. Aim: To evaluate the effectiveness of thymus honey on radiation induced-oral mucositis and xerostomia. The specific objectives of the research are to evaluate: 1) the quality of life of patients with head and neck malignancy before and after the intervention 2) the effectiveness of the use of honey to maintain the ideal weight of patients, 3) the possible reduction of the degree of xerostomia and oral mucositis and 4) the pain in the mouth after the intervention. Μethods: This is a randomized control trial. The survey was conducted in Cyprus Oncology Centre and the participants included in the study were 72 patients with any form of malignant head and neck cancer undergoing radiotherapy in the oral cavity during the period January 2012 - January 2014. Group A / experimental group except of medication followed for the prevention and treatment of xerostomia and oral mucositis followed the research protocol included mouthwashes with honey. In group B / group control patients used the usual prescription medication that is used for dry mouth and oral mucositis in combination with oral rinses with saline. All patients completed 3 questionnaires at three time periods before the start of the intervention, after the completion of radiotherapy, and 6 months after radiotherapy (total 3 times). Two scales of the objective evaluation of xerostomia and oral mucositis were used weekly throughout the intervention, and in addition, been undertaken weekly weighing of patients for monitoring the change in weight. Results: Through analysis of variance with repeated measures (Repeated measures ANOVA) revealed a statistically significant effect of the intervention involved the objective assessment of oral mucositis (F = 11,064 p <0,0001) and xerostomia (F = 9,06 p <0,0001 ). Also, there was a statistically significant effect of the intervention both, the objective assessment of body weight of the patients (F = 36,09, p <0,0001) and the subjective assessment of pain (F = 7.24 p = 0.001). After the start of the intervention showed significantly affecting the improvement in most aspects of general quality of life of participants in the intervention Conclusions: The results of this study provide strong evidence that the use of honey in the form of mouthwash, can contribute positively to the stabilization and improvement of oral mucositis and xerostomia that confront head and neck cancer patients during and after the completion of their treatment. Moreover, it seems that it can help reduce oral pain, stabilize the weight of patients and improve the overall quality of life.
Keywords: Head and Neck Malignancy; Malignancy; Oral Mucositis; Κακοήθεια Κεφαλής και Τραχήλου; Κακοήθεια; Στοματική Βλεννογονίτιδα